Conscientious objection and abortion in Chile - Marshall, Pablo (2020)
This paper critically analyzes conscientious objection in the context of the new regulation of pregnancy termination in Chile. It affirms that adequate regulation should not be blind to the hostile context in which abortion rights have been enacted and the difficulties experienced. The bioethical requirements that seek to balance the interests involved must consider the legal regulation of the interests at stake, the context in which they are implemented and, fundamentally, the effectiveness of the solutions adopted. Attention should be paid to the risks involved in the proliferation of objections that are not serious and to the political use of conscientious objection to prevent the implementation of women’s reproductive rights. In describing the process of entrenchment, strengthening and expansion of the conscientious objection in Chile, we show how this process has overprotected consciousness and the risks of undermining the effectiveness of the new abortion law, hindering and dilating the enjoyment of rights entrenched by the law. In response, regulatory measures are proposed to reverse this situation, which are obtained mainly from the bioethical literature on the subject and that look at the adverse context of the guarantee of women’s sexual and reproductive rights.